2018
DOI: 10.2196/mhealth.9218
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness of a Smartphone App for Improving Healthy Lifestyles in General Population in Primary Care: Randomized Controlled Trial (Evident II Study)

Abstract: BackgroundInformation and communication technologies are currently among the supporting elements that may contribute to improving health and changing lifestyles.ObjectiveThe aim of this study was to evaluate the long-term effectiveness of adding an app to standardized counseling in order to increase physical activity (PA) and adherence to the Mediterranean diet and to analyze the effects of app adherence in lifestyle changes.MethodsA randomized, multicenter clinical trial with a 12 month-follow up was conducte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 27 publications
(43 reference statements)
0
64
0
1
Order By: Relevance
“…For a small number of users in Lin et al [59], feedback decreased PA because of emotional connections to the avatar (fish), which backfired because users stopped checking when they saw their fish was sad. Feedback in Duncan et al [19] and Garcia-Ortiz et al [134] was non-significant, but unfortunately, no explanation for the absence of effects was provided.…”
Section: Feedbackmentioning
confidence: 89%
See 2 more Smart Citations
“…For a small number of users in Lin et al [59], feedback decreased PA because of emotional connections to the avatar (fish), which backfired because users stopped checking when they saw their fish was sad. Feedback in Duncan et al [19] and Garcia-Ortiz et al [134] was non-significant, but unfortunately, no explanation for the absence of effects was provided.…”
Section: Feedbackmentioning
confidence: 89%
“…From a vote counting perspective, of 14 quantitative studies, 12 versus 2 [19,134] studies showed significant, positive effects of feedback on PA [17,55,77,86,89,120,122,123,127,129,133,135]. The remaining 18 studies reported qualitative, supporting results.…”
Section: Feedbackmentioning
confidence: 96%
See 1 more Smart Citation
“…Of 17 articles published from 2014 to 2019, more than half ( n = 10) obviously presented the use of mobile technologies (e.g. smartphone, tablet) [ 21 , 28 , 30 , 31 , 34 , 39 , 40 , 42 , 51 , 52 ], while some programmes were potential to access by mobile devices (Table 2 and Additional file 2 ) [ 20 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The research group in the Netherlands produced ‘It’s LiFe!’ as an intervention for promoting PA in PHC [ 31 , 34 , 39 ]. The Spanish team introduced a randomised controlled trial to investigate the short- and long-term effects on utilisation of a mobile phone app [ 40 , 42 ]. The online programme, MyPlan 1.0, developed in Belgium was presented in two articles (Table 2 and Additional file 2 ) [ 20 , 32 ].…”
Section: Resultsmentioning
confidence: 99%